Chinese nutrition therapy : dietetics in traditional Chinese medicine (TCM) - Kastner, Jörg, 1963- (Thieme, 2004)
Kastner's Chinese Nutrition Therapy is an excellent introduction to Chinese dietetics for both, students and practitioners of Chinese medicine. - I wholeheartedly endorse his book. Nigel Wiseman For millennia, the Chinese have taught that a healthy, appropriate diet is an integral part of maintaining good health and healing myriad disorders, from the common cold and morning sickness to heart disease and diabetes.
"An authorized and revised translation of the 2nd German edition revised and copyrighted 2003 by Hippokrates Verlag, Stuttgart, Germany"--Title page verso
Keywords: Dietetics.; Medicine, Chinese.; Diet therapy.; Nutrition.; Diet in disease.; Nutrition Therapy -- methods; Diet; Medicine, Chinese Traditional; Nutritional Physiological Phenomena; Diététique.; Médecine chinoise.; Diétothérapie.; Régimes alimentaires.; HEALTH & FITNESS -- Nutrition.; HEALTH & FITNESS -- Diets.; MEDICAL -- Nutrition.; MEDICAL -- Nursing -- Nutrition.; HEALTH & FITNESS -- Food Content Guides.; Diet in disease; Diet therapy; Dietetics; Medicine, Chinese; Nutrition